2018
DOI: 10.3390/jcm7110444
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Splice Variant 7 Drives the Growth of Castration Resistant Prostate Cancer without Being Involved in the Efficacy of Taxane Chemotherapy

Abstract: Expression of androgen receptor (AR) splice variant 7 (AR-V7) has been identified as the mechanism associated with the development of castration-resistant prostate cancer (CRPC). However, a potential link between AR-V7 expression and resistance to taxanes, such as docetaxel or cabazitaxel, has not been unequivocally demonstrated. To address this, we used LNCaP95-DR cells, which express AR-V7 and exhibit resistance to enzalutamide and docetaxel. Interestingly, LNCaP95-DR cells showed cross-resistance to cabazit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
(67 reference statements)
1
10
0
Order By: Relevance
“…21,22 Similar to docetaxel, cabazitaxel produced dose-dependent cytotoxicity in each cell-line tested: PC3 cells with an IC 50 value of 1.6 nM ( Figure 5A); DU-145 cells with an IC 50 value of 0.2 nM ( Figure 5B); and 22Rv1 cells with an IC 50 value of 0.3 nM ( Figure 5C); similar to previously published literature. 32,33 Combination of cabazitaxel with SBFI-102 or SBFI-103 resulted in greater cytotoxicity in all three cell-lines than each drug when administered alone ( Figure 6). CI values were calculated across a range of cabazitaxel concentrations, and synergistic relationships between cabazitaxel and the FABP5 inhibitors were observed (Table 2).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…21,22 Similar to docetaxel, cabazitaxel produced dose-dependent cytotoxicity in each cell-line tested: PC3 cells with an IC 50 value of 1.6 nM ( Figure 5A); DU-145 cells with an IC 50 value of 0.2 nM ( Figure 5B); and 22Rv1 cells with an IC 50 value of 0.3 nM ( Figure 5C); similar to previously published literature. 32,33 Combination of cabazitaxel with SBFI-102 or SBFI-103 resulted in greater cytotoxicity in all three cell-lines than each drug when administered alone ( Figure 6). CI values were calculated across a range of cabazitaxel concentrations, and synergistic relationships between cabazitaxel and the FABP5 inhibitors were observed (Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…Cabazitaxel (Figure D) is a second‐line chemotherapeutic for advanced metastatic PCa, and is often utilized after tumors begin to develop docetaxel‐resistance . Similar to docetaxel, cabazitaxel produced dose‐dependent cytotoxicity in each cell‐line tested: PC3 cells with an IC 50 value of 1.6 nM (Figure A); DU‐145 cells with an IC 50 value of 0.2 nM (Figure B); and 22Rv1 cells with an IC 50 value of 0.3 nM (Figure C); similar to previously published literature . Combination of cabazitaxel with SBFI‐102 or SBFI‐103 resulted in greater cytotoxicity in all three cell‐lines than each drug when administered alone (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the outcomes of CRPC were significantly superior in the enzalutamide than the flutamide group, in terms of the PSA response. However, owing to the challenges in treating enzalutamide-and taxane-resistant CRPC, other therapeutic strategies need to be established and validated before enzalutamide initiation [21].…”
Section: Discussionmentioning
confidence: 99%
“…In human PCa cell lines, expression of AR-V7 mediates resistance to a new generation of AR-targeted therapies, such as enzalutamide and abiraterone [53]. In addition, Shimizu et al recently reported that knockdown of AR-V7 in LNCaP95-DR cells did not restore sensitivity to docetaxel and cabazitaxel, suggesting that AR-V7 may be not involved in taxane resistance [54]. Thus, expression of AR-V7 has been proposed for the assessment of suitability for taxane chemotherapy [55].…”
Section: Discussionmentioning
confidence: 99%